Pengaruh Analisis Fundamental Dan Analisis Teknikal Terhadap Keputusan Pembelian Saham PT. Industri Jamu Dan Farmasi Sido Muncul Tbk (SIDO) - Randy Aulia Firdaus; Yanda Bara Kusuma (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This study aims to analyze the influence of fundamental analysis and technical analysis on stock purchase decisions of PT Industri Jamu dan Farmasi Sido Muncul Tbk (SIDO). Fundamental analysis and technical analysis are two approaches that are often used by investors in making stock investment decisions. This study uses a quantitative method with multiple linear regression analysis techniques. Data were obtained through questionnaires distributed to 100 SIDO stock investors. The results showed that fundamental analysis and technical analysis partially have a significant effect on SIDO stock purchase decisions. Simultaneously, both types of analysis also have a significant effect. Fundamental analysis has the most dominant influence on SIDO stock purchase decisions compared to technical analysis. Investors are advised to consider both types of analysis in making stock investment decisions in order to make the right decisions.